2021
DOI: 10.3389/fped.2021.675775
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between High Birth Weight and Long-Term Outcomes—Implications for Assisted Reproductive Technologies: A Systematic Review and Meta-Analysis

Abstract: Background: Studies have shown that the prevalence of children born with high birth weight or large for gestational age (LGA) is increasing. This is true for spontaneous pregnancies; however, children born after frozen embryo transfer (FET) as part of assisted reproductive technology (ART) also have an elevated risk. In recent years, the practice of FET has increased rapidly and while the perinatal and obstetric risks are well-studied, less is known about the long-term health consequences.Objective: The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 196 publications
(271 reference statements)
0
28
0
1
Order By: Relevance
“…Finally, fetal programming in GDM has been studied in the context of DOHaD hypothesis (developmental origins of health and disease) to understand the long-term consequences of growing in a hyperglycemic environment during life in utero. Hyperglycemia and maternal obesity generate epigenetic changes in fetal programming, increasing the risk for obesity, T2DM, impaired glucose tolerance, insulin resistance, coronary heart disease, chronic arterial hypertension, dyslipidemia, metabolic syndrome, and some cancers in the future life of the newborn [ 3 , 323 , 324 , 325 , 326 , 327 ]. Interestingly, it has been observed that GDM effects in childhood are manifested after two years of age, such as an increase in BMI and hyperglycemia [ 328 ].…”
Section: Adverse Perinatal Outcomes Related To Gdmmentioning
confidence: 99%
“…Finally, fetal programming in GDM has been studied in the context of DOHaD hypothesis (developmental origins of health and disease) to understand the long-term consequences of growing in a hyperglycemic environment during life in utero. Hyperglycemia and maternal obesity generate epigenetic changes in fetal programming, increasing the risk for obesity, T2DM, impaired glucose tolerance, insulin resistance, coronary heart disease, chronic arterial hypertension, dyslipidemia, metabolic syndrome, and some cancers in the future life of the newborn [ 3 , 323 , 324 , 325 , 326 , 327 ]. Interestingly, it has been observed that GDM effects in childhood are manifested after two years of age, such as an increase in BMI and hyperglycemia [ 328 ].…”
Section: Adverse Perinatal Outcomes Related To Gdmmentioning
confidence: 99%
“…A large epidemiological study performed by our group using the Swedish population-based registers, compared 43 506 children born after ART vs 2 847 108 naturally conceived children and found a significantly increased risk of infant mortality from birth up to 1 year of life in singletons after ART, specifically when FETs were applied ( Rodriguez-Wallberg et al, 2020 ). High birthweight and large children for gestational age have been associated exclusively with FET in previous European studies ( Magnusson et al, 2021 ; Westvik-Johari et al, 2021 ). All these findings have been identified early in life and the long-term consequences when the ART population becomes older are unknown.…”
Section: Introductionmentioning
confidence: 62%
“…Dopiero później rozpoczęto dłuższą (6-7-dniową) hodowlę zarodków ludzkich do stadium blastocysty. Zaś, w zeszłym roku doczekaliśmy się szczegółowych opracowań wykazujących, że problem zwiększonej masy płodu i wynikających z tego powikłań pourodzeniowych, ma miejsce również w przypadku wydłużonej hodowli zarodków ludzkich [174,175]. Nasuwa się pytanie: czy można było uniknąć tych problemów u ludzi i nie stosować wydłużonej hodowli zarodków ludzkich w oparciu o wcześniejsze alarmujące wyniki prac na zwierzętach?…”
Section: Uwagi Końcoweunclassified